Daisy Fay and the miracle man - Flagg, Fannie (Ballantine reader's circle., 2005)
"Daisy Fay Harper turns 17 during the 1950s, and her experiences evoke the time in the deep South of strapless net evening gowns and Red Ryder"--NoveList.